Searching for Factors Contributing to Students’ Intention to Become a Leader: Internal Factors vs. Influence from Others - Eka Gatari; Nurul Arbiyah (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2018)
Leadership development within universities in Indonesia is still lacking, even though it is important as a starting point to develop future leaders. This study is aimed at exploring factors which might affect a students’ intention to become a leader in a student organization, namely, attitude toward student leadership, subjective norms, perceived behavioral control, and leadership self-efficacy. Second- and third-year students (N = 286) from various faculties in a state university filled in a paper-based questionnaire containing newly constructed measurements, based on the theory of planned behavior by Ajzen and the theory of self-efficacy by Bandura. Data analysis using hierarchical multiple regression showed that only the subjective norms were related to the students’ intention to lead student organizations (β = .45, p < .01). This result implied that student organizations should also consider the potential leaders’ peers, families, and significant others to persuade them to become leaders. Other implications were discussed further.